The role of physical activity, diet, and stress management in maternal and infant health during pregnancy - Bartosz Pawłowski; Aleksandra Madej; Karolina Haczkur-Pawłowska; Kacper Jasiński; Alicja Kowal; Julia Malczewska; Kornelia Fiszer; Aleksandra Łomża-Łaba; Stanisław Dziurda; Grzegorz Jama (Nicolaus Copernicus University in Toruń, 2024)
Introduction and aim of the study: During pregnancy, significant physiological, hormonal and circulatory changes occur that affect both the health of the mother and the child. Therefore, it is important for the mother to maintain physical activity, a healthy diet, and reduce stress to prevent complications and health problems for the mother and the child. Material and Methods: The Pubmed database was searched. The criteria for qualifying the article for the review were the following keywords: pregnancy, exercise, rehabilitation, nutrition during pregnancy, postpartum depression, atopy, stress, asthma. 30 articles from 2002-2023 were analyzed. Description of the state of knowledge: Regular physical activity during pregnancy brings many benefits such as reducing the risk of complications during childbirth, postpartum depression and helps to maintain a healthy body weight. Diet also has an impact on the health of both mother and baby. It should be balanced, providing the necessary nutrients and taking into account the mother's caloric needs. It is very important to reduce stress due to its negative impact on the mother and child. Summary: Physical activity and a healthy diet directly affect the course of pregnancy and the health of the fetus and baby. Exercise prevents pregnancy complications and other diseases, and maternal nutritional status is critical for fetal growth. During pregnancy, women are exposed to stress, which can be the cause of chronic mental disorders. Depression is the most common mental illness that occurs during pregnancy, which is influenced by various factors. In addition, maternal stress has a negative impact on the child's health, potentially increasing the risk of a number of atopic and non-atopic diseases.